If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 4 + -5x * 1 = 4 Reorder the terms for easier multiplication: x + 4 + -5 * 1x = 4 Multiply -5 * 1 x + 4 + -5x = 4 Reorder the terms: 4 + x + -5x = 4 Combine like terms: x + -5x = -4x 4 + -4x = 4 Add '-4' to each side of the equation. 4 + -4 + -4x = 4 + -4 Combine like terms: 4 + -4 = 0 0 + -4x = 4 + -4 -4x = 4 + -4 Combine like terms: 4 + -4 = 0 -4x = 0 Solving -4x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '-4'. x = 0 Simplifying x = 0
| x+81=8x-7 | | 0.13x=0.08x+26 | | 48x^2-675=0 | | 3x-5=2(3x-6) | | 4x-2(x-2)=-8+4x+6 | | 10p-95=p+31 | | 6(x-5)=5 | | .27(x+2)=42 | | 9a=9a | | 125+x+15=180 | | 3x+-2=4x+5 | | -42y=66 | | 42y=66 | | -8x-5y=-11 | | 81-x=27 | | 9a=a+60 | | 2b-b^2-15=0 | | 2(2x-8)-5=2(x-3)-1 | | 78507+11.25x=20885+23x | | 6N+6J=N | | 2a-11=3(a+1)+16a+5 | | 3x^2-13w-6w^2=0 | | v=2v-73 | | 7n+6=13+7n | | 16=-2(x+4) | | 5-13w-6w^2=0 | | 4u+18=2u+66 | | 0.20=ln(y) | | .25(x+4)=32 | | 9x^2-36=y | | 8u^2+1u-9=0 | | 28-8k=4(-1-k) |